A comparison of the hilots' pressure points and acupuncture points - Marana, Ma. Rebecca V.
This research is a comparative study of the hilots' pressure points and acupuncture points taking into consideration the following aspects: general characteristics, location, indications, uses, technique (amount of pressure applied, duration of application of pressure, method of massage, frequency of treatment, medium used in massage and precautions and contraindications). 5 hilots residing in Lipa City and Davao City were observed at 5 different sessions each, while treating patients. Instrument used were an interview schedule, a checklist, anatomical drawings and validation by the researcher. A descriptive analysis of the data gathered was done after the findings had been collected and summarized. This paper also aims to find the similarities and differences between the hilots' concept of the mechanism of massage and that of the theoretical of acupuncture. The findings of the study are as follows: 1. Pressure areas of the hilots, like acupuncture points are tender and sore in a diseased state. These pressure points of the hilots are hard and leather-tough on palpation. In terms of size, they are actually more of areas rather than points. Nomenclature of these pressure points is dependent on the part of the body where they are located e.g. likod (back), dibdib (chest) etc. 2. The location of pressure areas of the hilots depends on where the bara (blockage) has been determined. Location, therefore, of the points is not fixed. These pressure were found, however, to coincide with acupuncture points. 3. Pressure areas of the hilots have generally no specific indications. Massage, though, is generally indicated for pilay or pasma. 4. Pressure areas of the hilots are mainly used for treatment. Use of pressure areas for preventive and diagnostic purposes was not observed. 5. In terms of technique, the hilots do not have any specific directions for massage nor do they have any definite time for treatment. The amount of pressure applied on body areas is dependent on what the patient can tolerate. Frequency of treatment is 1 to 3 sessions, usually every other day, regardless of whether the ailment is acute. The hilots refrain from applying in the following: full or empty stomach, hypertension and rheumatism.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Traditional medicine; Acupuncture points; Hilots